Strengthening the West African Economic and Monetary Union : The Role of Fiscal and Market Institutions in Economic Stabilization - Basdevant, Olivier (Departmental Papers; Departmental Paper ;, 2015)
West African Economic and Monetary Union (WAEMU) countries face a well-known dilemma between the need to provide shock-smoothing mechanisms and the lack of adequate mechanisms to do so. WAEMU countries are subject to frequent and, to a large extent, asymmetric shocks. They have remained poorly diversified and vulnerable to external shocks, such as changing weather conditions. In addition to limited shock-smoothing mechanisms at the regional level, WAEMU members' ability to respond to shocks through national policies is also constrained by limited fiscal space and the need to preserve external stability-not only at the national level but also at the union level. In this context, developing a well-defined fiscal rule framework at the national level would help to build the necessary fiscal space for shock-smoothing. In addition, the development of specific shock-smoothing mechanisms-including a more developed and integrated financial sector-would also be critical. In addition, promoting financial development is also a challenge, which needs to be addressed in tandem with an adequate surveillance system. Some of these challenges have been faced by other monetary unions, such as the euro area.